Malignant primary female genital system lymphoid - Jia, Qiucheng; Tang, Huimin; Dong, Zhiyong; Chen, Wanying; Chen, Mengyue; Wei, Weiwei (Frontiers in Oncology, 2024)
Lymphoma is a malignant tumour of the lymphatic system with an incidence rate of about 6.6 per 100,000 people. Among the many lymphoma types, the most common is non-Hodgkin’s lymphoma. Lymphomas are common in the gastrointestinal tract, breast, neck, etc., while those in female genital tracts are rare. In this article, we report four cases of primary female genital system lymphoid malignancies diagnosed and treated at our hospital from 2018 to 2023, with a systematic review.